Strengthening the Role of Husbands in Preventing Anemia Among Pregnant Women in 2025 - Faradita Wahyuni; Dika Saraswati; Vicky Arfeni Warongan; Wynda Myke Nola (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2025)
Background: Anemia in pregnant women is a significant health concern that can increase the risk of pregnancy and childbirth complications. One of the key determinants in anemia prevention is the involvement of husbands. Objective: This study aimed to assess the improvement in husband participation in the prevention of anemia among pregnant women following an educational intervention at Hayati Clinic, Marelan, in 2025. Methods: A pre-experimental design with a one-group pretest-posttest approach was used. The sample consisted of 30 pregnant women and their husbands. The intervention included direct education and the distribution of informational leaflets. Data were analyzed descriptively and using paired t-tests. Results: The average score of husband participation increased from 2.48 to 4.14 after the intervention. All aspects of husband involvement showed a significant improvement (p < 0.05). Conclusion: Educational interventions for husbands are effective in enhancing their participation in the prevention of anemia during pregnancy.